Surface Engineering for Dental Implantology: Favoring Tissue Responses Along the Implant - Van Oirschot, Bart A.J.A.; Zhang, Yang; Alghamdi, Hamdan S.; Cordeiro, Jairo M.; Nagay, Bruna E.; Barao, Valentim A.R.; De Avila, Erica Dorigatti [UNESP]; Van Den Beucken, Jeroen J.J.P. (SAGE Publications, 2022)
Dental implants represent an illustrative example of successful medical devices used in increasing numbers to aid (partly) edentulous patients. Particularly in spite of the percutaneous nature of dental implant systems, their clinical success is remarkable. This clinical success is at least partly related to the effective surface treatment of the artificial dental root, providing appropriate physicochemical properties to achieve osseointegration. The demographic changes in the world, however, with a rapidly increasing life expectancy and an increase in patients suffering from comorbidities that affect wound healing and bone metabolism, make that the performance of dental implants requires continuous improvement. An additional factor endangering the clinical success of dental implants is peri-implantitis, which affects both the soft and hard tissue interactions with dental implants. In this study, we shed light on the optimization of dental implant surfaces through surface engineering. Depending on the region along the artificial dental root, different properties of the surface are required to optimize prevailing tissue response to facilitate osseointegration, improve soft tissue attachment, and exert antibacterial efficacy. As such, surface engineering represents an important tool for assuring the continued future success of dental implants. Dental implants represent a common treatment modality nowadays for the replacement of lost teeth or fixation of prosthetic devices. This review provides a detailed overview of the role of surface engineering for dental implants and their components to optimize tissue responses at the different regions along the artificial dental root. The surface properties steering immunomodulatory processes, facilitating osseointegration, and rendering antibacterial efficacy (at both artificial root and abutment region) are described. The review finally concludes that surface engineering provides a tool to warrant that dental implants will remain future proof in more challenging applications, including an aging patient population and comorbidities that affect bone metabolism and wound healing.
Keywords: antibacterial; dental implant; osseointegration; peri-implantitis; surface engineering; tissue response